2000
DOI: 10.1523/jneurosci.20-02-00626.2000
|View full text |Cite
|
Sign up to set email alerts
|

Switching Off and On of Synaptic Sites atAplysiaSensorimotor Synapses

Abstract: Using the highly plastic synapses between mechanoreceptor sensory neurons and siphon motor neurons of Aplysia as a model, we have investigated whether switching off and on of individual synaptic release sites is a strategy that is used by neurons in forms of short-term synaptic modulation with a time course of minutes to hours. We have modified some of the techniques of classical quantal analysis and examined the kinetics of synaptic depression under different stimulation protocols to answer this question. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
41
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 54 publications
4
41
2
Order By: Relevance
“…It was proposed that Ca triggers vesicles mobilization from the reserve pool to the ready-releasable pool and that this process is controlled by synapsins (Humeau et al 2001;Zucker and Regehr 2002;Fioravante et al 2007). Other mechanisms such as modulation of the efficacy of release mechanisms and switching on individual synaptic release sites were also proposed to contribute to PTP (Royer et al 2000;Zhao and Klein 2004;Humeau et al 2007;Korogod et al 2007). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was proposed that Ca triggers vesicles mobilization from the reserve pool to the ready-releasable pool and that this process is controlled by synapsins (Humeau et al 2001;Zucker and Regehr 2002;Fioravante et al 2007). Other mechanisms such as modulation of the efficacy of release mechanisms and switching on individual synaptic release sites were also proposed to contribute to PTP (Royer et al 2000;Zhao and Klein 2004;Humeau et al 2007;Korogod et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…At excitatory synapses, depletion of the readily releasable vesicle stores by high-frequency stimulation has been recognized as a major cause of short-term synaptic depression (Model et al 1975;Rosenmund and Stevens 1996;Weis et al 1999;Wu and Borst 1999). Inactivation of presynaptic Ca 2+ currents and other downstream mechanisms that lower the release probability were also proposed to account for homosynaptic depression (Patil et al 1998;Wu and Borst 1999;Royer et al 2000;Gover et al 2002;Xu et al 2007). Short-term synaptic enhancement, on the other hand, is attributed to a number of activity-dependent mechanisms including enhanced calcium (Ca) influx (Jackson et al 1991;Geiger and Jonas 2000;Habets and Borst 2005), reduced Ca buffering (Blatow et al 2003;Felmy et al 2003), increased channel-vesicle coupling, or increased Ca sensitivity of the vesicle fusion mechanisms (Korogod et al 2007).…”
mentioning
confidence: 99%
“…Stimuli sufficient to elicit withdrawal reflexes evoke a high-frequency burst of spikes in the SNs (Byrne et al 1978a,b;Walters et al 1983;Stopfer and Carew 1996;Frost et al 1997;Antonov et al 1999;Phares et al 2003). Such bursts of SN activity induce homosynaptic depression of the sensorimotor synapses, a mechanism that limits the response of MNs to peripheral stimuli (Byrne et al 1978b;Walters et al 1983;Stopfer and Carew 1996;Antonov et al 1999;Phares et al 2003).For the past thirty years, homosynaptic depression of Aplysia sensorimotor synapses has been attributed exclusively to presynaptic mechanisms Byrne 1982;Gingrich and Byrne 1985;Bailey and Chen 1988;Eliot et al 1994;Armitage and Siegelbaum 1998;Royer et al 2000;Gover et al 2002;Zhao and Klein 2002). Moreover, it has been repeatedly suggested that homosynaptic depression of the sensorimotor synapse does not have a postsynaptic contribution Armitage and Siegelbaum 1998;Royer et al 2000).…”
mentioning
confidence: 99%
“…For the past thirty years, homosynaptic depression of Aplysia sensorimotor synapses has been attributed exclusively to presynaptic mechanisms Byrne 1982;Gingrich and Byrne 1985;Bailey and Chen 1988;Eliot et al 1994;Armitage and Siegelbaum 1998;Royer et al 2000;Gover et al 2002;Zhao and Klein 2002). Moreover, it has been repeatedly suggested that homosynaptic depression of the sensorimotor synapse does not have a postsynaptic contribution Armitage and Siegelbaum 1998;Royer et al 2000).…”
mentioning
confidence: 99%
See 1 more Smart Citation